The Effects of Shade and Light on Corals in the Context of Coral Bleaching and Shading Technologies - Tagliafico, Alejandro; Baker, Paul; Kelaher, Brendan; Ellis, Sophia; Harrison, Daniel (Frontiers in Marine Science, 2022)
The current coral reefs crisis is motivating a number of innovative projects attempting to leverage new mechanisms to avoid coral bleaching, reduce coral mortality and restore damaged reefs. Shading the reef, through seawater atomised fogging, is one tool in development to reduce levels of irradiance and temperature. To evaluate the potential viability of this concept, here we review 91 years (1930–2021) of published research looking at the effects of different levels of shade and light on coral reefs. We summarised the types of studies, places, coral species used, common responses variable measured, and types of shades used among studies. We discuss issues related to reef scale shading applicability, different methods used to measure light, standardisation methods and most importantly the positive and negative effects of shading corals.